Microbial indoor air pollution in Delhi Metropolitan City is attributable to severe respiratory and general health effects among residents - Kumar, Pradeep; Singh, Rajeev (Frontiers in Public Health, 2025)
Indoor air quality plays a crucial role in the health and well-being of residents. Delhi, known as one of the most polluted cities globally, often receives insufficient attention in managing and mitigating related health impacts. This study isolated, characterized, and assessed microbial indoor air quality (bioaerosols) using multiproxy approaches and correlated findings with associated health effects. The spatial variation of bacterial aerosols showed irregular patterns, increasing from winter to summer and decreasing in fall; fungal aerosols consistently increased from winter to fall. Bacterial aerosol concentrations ranged from 730 to 5,300 CFU/m3, while fungal concentrations were between 1,330 and 6,050 CFU/m3, significantly exceeding the recommended limits. The size distribution of fungal aerosols varied across seasons, with higher concentrations in the 4th and 5th stages of the sampler. Several airborne bacterial and fungal genera, including Staphylococcus, Streptococcus, Micrococcus, Aspergillus, Penicillium, and Cladosporium, were identified in homes. Health effects were most pronounced in winter followed by fall, with symptoms such as headaches, eye irritation, allergic rhinitis, coughing, and sneezing being common. As per this study, there may be a correlation between indoor bioaerosol concentrations, seasonal variations, and health outcomes, though further in-depth in vitro, exposure assessment, and epidemiological studies are necessary to substantiate these findings.